Influences of cutting parameters on surface roughness of SiCp/Al composites. Issue 3 (January 2021) - Wang, J L; Huang, S T; Pang, B; Li, H B
Abstract: Poor surface roughness may reduce the safety and the stability of the parts, to analyse the relationship between cutting parameters and surface roughness is significative to increase the machining quality of SiCp/Al composites. In this paper, the influences of tool rake angle, cutting speed and cutting depth on the surface roughness of SiCp/Al composites were studied by the two dimension cutting experiments. The Ra values were measured by using type TR200 roughness machine. The results indicate that tool rake angle and cutting depth are the main parameters which affect the surface roughness while cutting speed has no significant effects on the surface roughness.